Tuesday
March 28, 2017

Post a New Question

Posted by on .

how would i solve this using the substitution method

3y=11-x
3x-y=3

thanks

  • math - algebra - ,

    Substitute 11 -3y for x in the second equation.
    Why? Because the first equation tells you that
    x = 11 -3y.

    You should get
    3(11 -3y)= 3 + y
    33 - 9y = 3 + y
    10y = 30
    y = ___ ?

    Then solve for x, using either of the first two equations you were given.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question